EFEKTIVITAS MANAJEMEN KELAS DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI MTs MARAQITTA’LIMAT TIRPAS - Sahabudin Sahabudin; Alpi Zaidah; Fena Prayunisa (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2024)
Classroom management is an important factor in the learning process that can influence the quality and quantity of student learning outcomes. Class management can make students feel comfortable and enthusiastic in receiving learning material. With these conditions, it is hoped that student learning achievement will increase. The aim of this research is to find out how class VIII is managed at MTs Maraqitta'limat Tirpas, what is the learning achievement of class VIII students at Mts Maraqitta'limat Tirpas and what are the inhibiting factors in implementing class management in improving student learning outcomes. achievement in class VIII MTs Maraqitta'limat Tirpas. The research used is field research with a Qualitative Naturalistic approach. The choice of this method is based on the consideration that what you want to look for is data that provides concrete descriptions and paintings of complex social realities. At MTs Maraqitta'limatTirpas there is still a lack of student interest in learning during learning which is caused by poor classroom control carried out by teachers during the learning process which results in student learning achievement decreasing. The learning achievements of students at MTs Maraqitta'limat Tirpas are quite good because there are many achievements obtained at MTs Maraqitta'limat Tirpas, for example the implementation of MTQ at the National level, if you look at class VIII there are also many such achievements. such as holding mathematics olympiads and so on.